Pore pressure and reservoir quality evolution in the deep Taranaki Basin, New Zealand. (December 2018) - O'Neill, Sean R.; Jones, Stuart J.; Kamp, Peter J.J.; Swarbrick, Richard E.; Gluyas, Jon G.
Abstract: The Palaeocene fluvial to shallow marine sandstones of the Farewell Formation are an important proven hydrocarbon reservoir in the Taranaki Basin, New Zealand. The Kapuni Deep-1 well was drilled to target Farewell Formation sandstones in the deeper overpressured (>5000 m, >3000 psi/21 MPa) sections of the onshore Manaia Graben of the Taranaki Basin. However, the Farewell Formation sandstones display anomalously low measured helium porosities (1–4.5%) and intergranular volumes (6–11%) even for their present-day, close to maximum, burial depth (c.5000 m). One dimensional burial history modelling demonstrates initial rapid burial leading to significant porosity reduction via mechanical compaction, enhanced by poor sorting, angular grain morphology and the presence of ductile grains, which allowed efficient packing and plastic deformation. Low intergranular volume (IGV), anhedral nature of quartz overgrowths, a general lack of fluid inclusions, and poor crystalline clay mineral content indicate that early burial compactional processes significantly influenced reservoir quality. The lack of mudstone to siltstone grade lithologies within the overlying Eocene section inhibited the early or shallow onset of overpressure in the Farewell Formation. One dimensional basin modelling has shown that rapid Pliocene subsidence related to exceptionally high sedimentation rates generated overpressure through disequilibrium compaction in the overlying Oligocene to early Miocene section during the past 6 Ma. However, the late and deep (>3000 m) onset of overpressure had no effect on arresting porosity loss in the Farewell Formation. Continued compaction of Farewell Formation sandstones after dissolution of early carbonate cements of CO2 rich fluids creates zones of extremely low permeability, which have the potential to act with interbedded shales to form pressure seals as seen in the Kapuni Field. Highlights: High vertical effective stress drives porosity reduction in the deep Taranaki Basin. Onset and development of overpressure is defined through 1D basin modelling. Porosity and intergranular volume is anomalously low for present burial depth. Vertical pressure seals within sandstones are identified.